2019
DOI: 10.3390/ijms20061415
|View full text |Cite
|
Sign up to set email alerts
|

Robust Identification of Suitable T-Cell Subsets for Personalized CMV-Specific T-Cell Immunotherapy Using CD45RA and CD62L Microbeads

Abstract: Viral infections and reactivations remain a serious obstacle to successful hematopoietic stem cell transplantation (HSCT). When antiviral drug treatment fails, adoptive virus-specific T-cell transfer provides an effective alternative. Assuming that naive T cells (TN) are mainly responsible for GvHD, methods were developed to generate naive T-cell-depleted products while preserving immune memory against viral infections. We compared two major strategies to deplete potentially alloreactive T cells: CD45RA and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…To characterize the involvement of different subsets of αβ CD4 conv , αβ CD8 + , and γδ T cells based on their antigen experience 18,19 , we developed a staining panel dedicated to identifying four distinct populations based on CD62L and CD45RA expression ( Supplementary Fig. 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the involvement of different subsets of αβ CD4 conv , αβ CD8 + , and γδ T cells based on their antigen experience 18,19 , we developed a staining panel dedicated to identifying four distinct populations based on CD62L and CD45RA expression ( Supplementary Fig. 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent report on adoptive virus-specific T cell transfer showed that the CD45RA-depleted population with loss of TEMRA cells substantially lost donor-specific immune responses. In contrast, the CD62L-depleted population with loss of TCM cells consistently yielded 3-5 folds higher donor Ag responses [44]. In addition, it has been reported that the main driving force behind AR is TEM cells in the transplant field [45].…”
Section: Discussionmentioning
confidence: 97%
“…IFN-γ ELISpot assay was performed as described previously [44,45]; details are provided in supplementary information (Methods, Tab.S3).…”
Section: Ifn-γ Elispotmentioning
confidence: 99%